Diverticulitis complicated by colovenous fistula formation and pylephlebitis. Issue 1 (14th January 2022) - Krzak, Ada Maria; Townson, Adam; Malam, Yogeshkumar; Mathews, John
Abstract: Acute diverticulitis is associated with a range of complications including fistula formation. Colovenous fistula formation, where there is a fistula between the inferior mesenteric vein and colon, is an extremely rare and serious complication of diverticulitis. Pylephlebitis, which is defined as infective suppurative thrombosis of the portal vein, is another uncommon complication of any intra-abdominal source of infection, including diverticulitis. Both complications are independently associated with significant morbidity and mortality. We report a case of a patient with acute diverticulitis who subsequently developed both colo-venous fistula and pylephlebitis and was successfully managed conservatively.